OFFICE EQUIPMENT MANIPULATION AND HUMAN RELATIONS SKILLS TRAINING NEEDS OF SECRETARIES OF PUBLIC ESTABLISHMENTS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study determined office equipment manipulation and human relations skills training needs of secretaries of public establishments in Anambra State. Two research questions guided the study and six hypotheses were tested at 0.05 level of significance. The descriptive survey design was used in the study. The population of the study comprised 89 secretaries in publicestablishments in Anambra State. The instrument for data collection was a structured questionnaire. The instrument was validated by three experts. A pilot test was conducted to ascertain the reliability of the instrument. Test of reliability on the instrument with Cronbach Alpha yielded coefficient values of 0.75 and 0.77. The data collected were analyzed using mean and standard deviation and inferential statistics (ANOVA and t-test). Findings revealed that the respondents needed training in equipment manipulation skills and human relations skills. Furthermore, the findings revealed that gender, educational qualifications and years of experience of the respondents did not significantly influence their mean ratings on the training needs of secretaries in public establishments in Anambra State. The researcher concludes that secretaries public establishments in Anambra State need training to develop their equipment manipulation and human resource skills. It was recommended among others, that administrators of public establishments should ensure that office equipment tools and facilities are readily made available for secretaries.
Keywords: Office Equipment Manipulation, Human Resource, Skills, Secretaries, Public Establishment